Central bank coordinated policies and bank market power: an insight from the African context - Daniel Ofori-Sasu; Elikplimi Komla Agbloyor; Emmanuel Sarpong-Kumankoma; Joshua Yindenaba Abor (Cogent Economics & Finance, 2023)
The paper examines the impact of central bank regulatory policies on market power in Africa. The study presents a representative sample of 52 African economies over the period 2006-2020. The study shows that the individual regulatory policies of the central bank (i.e. monetary and macro-prudential policies) enhance banks' market power. Also, it reveals that central bank regulatory policies are better coordinated, as complements, in achieving greater market power of banks in countries with strong central bank independence (CBI) framework. However, the coordinated policies are substitutes in determining bank's market power in countries with weak CBI framework. The policy implication is that the right policy mix of coordinated central bank regulatory policy framework is important in determining an optimal outcome of bank's market power in both an inclusive central bank (monetary-prudential) policy targeting economies and an independent policy targeting economies.
Keywords: E3; E5; E61; G21; L10; L51; M21; 330; Central bank independence and market power; Monetary and Macro-prudential policies